Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445588
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Emotion and Agency on Presence in Virtual Reality

Abstract: Figure 1: We manipulated emotion and agency through a 2x2 design. a) A scene in the Happiness park VE. b) The dog in the HNA condition. c) The dog in the HA condition interacting with the laser pointer. d) A scene in the Fear park VE. e) The creature in the FNA condition. f) The creature in the FA condition and the torch light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 74 publications
2
22
0
Order By: Relevance
“…Alternatively, it is possible that negative VE design mainly manipulates perceived fear but not joy, and vice-versa positive VE design mainly targets perceived joy but not fear. This assumption is supported by a recent study investigating the effects of emotions on the formation of presence (Jicol et al, 2021). The study showed that only the predominant emotion in a VE affects presence.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Alternatively, it is possible that negative VE design mainly manipulates perceived fear but not joy, and vice-versa positive VE design mainly targets perceived joy but not fear. This assumption is supported by a recent study investigating the effects of emotions on the formation of presence (Jicol et al, 2021). The study showed that only the predominant emotion in a VE affects presence.…”
Section: Discussionmentioning
confidence: 52%
“…The study revealed that presence is mostly influenced by emotional intensity and less by emotional valence (Jicol et al, 2021). Also, only the predominant emotion in a VE increased presence (Jicol et al, 2021). Presence describes the subjective sensation of being in a real place, i.e., accepting the VE as the current location, despite physically being in a different environment (Slater, 2009).…”
Section: Central Aspects Of Ve Designmentioning
confidence: 95%
See 2 more Smart Citations
“…Noticeably, the content designers of virtual environments bring a level of agency to their audiences. In virtual environments, agency refers to the extent to which users can interact and modify objects in the scenes [59]. Users with virtual environments of high agency levels can employ a more active approach when interacting with the empathic content to experience empathy.…”
Section: Facilitating Empathy In Xr and Metaversementioning
confidence: 99%